Properties of an electromagnetic twisted Gaussian Schell-model array beam propagating in anisotropic atmosphere turbulence - Yang, Xianyang; Fu, Wenyu; Hu, Xuehua; Li, Xue (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
The effect of anisotropic atmosphere turbulence on propagation characteristics of an electromagnetic twisted Gaussian Schell-model array (EM TGSMA) beam is investigated. An analytical expression for the cross-spectral density function of such beam propagating through anisotropic turbulent atmosphere is derived and used to explore the evolutionary behavior of the spectral intensity, degree of polarization (DOP) and degree of coherence (DOC). An example illustrates the fact that twisted strength and anisotropic turbulent factors have an important impact on the behavior of spectral density, DOC and DOP, in particular. The rotation angle of the array beams can also be controlled by adjusting twisted strength. Furthermore, strong anisotropic turbulence was also found to cause significant mergence of the array beams. Our results might be beneficial for free-space communications of the partially coherent beams endowed with twist.
Optica Applicata, Vol. 52, 2022, nr 4, s. 639-654
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; partially coherent; array beams; twist phase; anisotropic atmosphere turbulence; propagation properties